First record of \(Opisthotropis durandi\) Teynié, Lottier, David, Nguyen & Vogel, 2014 (Squamata: Natricidae) from Vietnam - Van Nghia, Ha; Ziegler, Thoma; Quang Truong, Nguyen; Duc Minh, Le; Quang Vinh, Luu (Academia Journal of Biology, 2023)
We provide the first country record of Opisthotropis durandi Teynié, Lottier, David, Nguyen & Vogel, 2014 from Vietnam based on a single snake specimen from Dien Bien province. The species previously was only known from the Lao People’s Democratic Republic (Laos). DNA sequence data of a male specimen from Vietnam match those of one a specimen of O. durandi from Phongsali province, Laos, and the newly collected individual from Vietnam also corresponds O. durandi in terms of diagnostic morphological features, except for a slightly higher ventral number (185 versus 177−181).